Diabetes mellitus in children and adolescents according to the Federal diabetes registry in the Russian Federation: dynamics of major epidemiological characteristics for 2013–2016 - Ivan I. Dedov (Endocrinology Research Centre, 2017)
Background: The data of the register is the main source of up-to-date information about patients with diabetes mellitus (DM). It’s very important for improving the quality of medical care organization. Aims: to analyze the main epidemiological DM characteristics in Russian Federation (RF) (prevalence, incidence, mortality) in children and adolescents, to assess the dynamics of these parameters for the period 2013 – 2016, to analyze the status of compensation for carbohydrate metabolism, therapy of DM1, prevalence of diabetic complications and the reasons for hospitalizations in these age groups. Materials and methods: The database of Federal DM registry of 81 regions was included in the online system. Results: The total number of patients under the age of 18 with DM in RF on 31.12.2016 was 33081 people, there were 95,9% (31727 people) with DM1 and 4,1% (1354 patients) with DM2. The prevalence of DM1 in 2013–2016 in children: 81.0 – 91.4 / 100 ths., in adolescents – 212,8–209,5 / 100 ths. The DM1 incidence/100 thousand population in 2016 in children was 14,2/100 ths., in adolescents 10,0/100 ths. HbA1c levels in DM1 was in children: <7,5% in 32%, 7,6–9,0% in 33%, >9% in 35% of the patients; in adolescents <7,5% in 25%, 7,6–9,0% in 30%, >9% in 45% of the patients. Among complications in children and adolescents with DM1, diabetic neuropathy is the most often recorded (in 10,9% of cases and 40,8%, respectively); among DM2 patients, diabetic neuropathy is registered in 4,7% and 8,8% in children and adolescents, respectively. There are associated diseases in DM2 patients – arterial hypertension and dyslipidemia. 43,8% of children and 49,2% of adolescents were hospitalized in the anamnesis, most hospitalizations in 2016 (children 71,9%, adolescents 67,1%) were due to diabetes. Conclusions: It is established that in the dynamics of 2013–2016 the prevalence of DM1 in children continues to increase, with relatively stable indicators in adolescents. According to the register, during last two years there has been a decrease in the incidence of DM1 and, on the contrary, an increase in the prevalence/incidence of DM2 in children. Significant interregional differences in the level of incidence/prevalence have been established, especially in regions located in various geographic regions of the RF. The frequency of diabetic complications in children and adolescents with diabetes varies. There is an association of hospitalizations with higher HbA1c level. In the structure of therapy of this age group the ratio of insulin therapy in syringes-pens and pump therapy is 80.9% / 15.1% according to the register.